Kebijakan Isolasionisme Presiden Trump dan Masa Depan Pangkalan Militer AS di Jepang - Umoro, Anisa Ledy (Universitas Muhammadiyah Yogyakarta, 2018)
The election of Donald Trump with his America First slogan has sent a signal that the new President is less interested in maintaining the position held by the United States as the leader on the international stage. This phenomenon raises questions about the United States’ commitment to its military presence outside its territory. By presenting the case of US military bases in Japan, this paper attempts to project the fate of these bases under the Trump presidency. At first glance, the President's inward-looking policy may seemingly trigger the future withdrawal of US troops from Japan. However, this article shall present an argument to the contrary: US military bases in Japan will survive the Trump presidency. To prove this argument; first, this article analyzes the reasoning behind the decision of a sending country to withdraw its military forces. Secondly, this article discusses what factors may underlie the decision of a host country to end military cooperation with the sending country. Finally, this paper analyzes the existence of mutual strategic factors. Although seven of these eight factors are supporting the continued presence of US military bases, one factor, namely President Trump's isolationist policy, shows that it may lead to the contrary. Nevertheless, this isolationist policy factor alone is not enough to end the existence of US military bases in Japan.